Analysis of Mathematical Problem Solving Ability Based on Self confidence in Creative Problem Solving Learning and Independent Learning Assisted Module . - Maliya, Nur; Sukestiyarno, Sukestiyarno (Unnes Journal of Mathematics Education Research, 2019)
The aim of this study are (1) to describe the quality of Creative Problem Solving learning, (2) to describe the problem solving ability based on self confidence in learning reative Problem Solving and independent learning assisted module, (3) to describe the ability to solve mathematical problems after applying Creative Problem Solving learning and independent learning. assisted by modules, (4) describe the influence of students' self knowledge on problem solving abilities. This study uses mixed methods with concurrent embedded models. The results of this study shown that the planning of learning to obtain the results is quite valid, the implementation of learning is in good category, and the average value of students' problem solving abilities in both classes reaches the minimum completenes criteria and the proportion of students who complete the minimum completenes criteria reaches 75%. Students with high Self confidence have been very good at solving problems with the right steps, students with Self confidence are already good enough in solving problems, students with low Self confidence still have difficulties in solving problems with the correct completion steps. Problem solving abilities after applied Creative Problem Solving learining and independent learning assisted mosules increased by 94,5% and 97,2%. There is an influence of Self confidence on both classes of 4.7% and 4.9%.